2021
DOI: 10.1136/bcr-2021-245792
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of herpes simplex keratitis following vaccination for COVID-19

Abstract: An 82-year-old man with a history of herpes simplex keratitis 40 years previously presented with recurrence, 1 day following vaccination for novel COVID-19. His condition worsened despite topical treatment with ganciclovir gel. A diagnosis of herpetic stromal keratitis was made, requiring systemic aciclovir, topical prednisolone, moxifloxacin and atropine, and oral doxycycline. He improved clinically on treatment, with some residual corneal scarring. Visual acuity improved from 6/36 corrected at presentation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 6 publications
0
33
0
1
Order By: Relevance
“…Keratitis in association with vaccines appeared to be uncommon. Furthermore, three cases of herpes simplex virus (HSV) keratitis were reactivated after COVID-19 vaccination (2 of 3 were associated with BNT162b2 mRNA vaccination, the third one was AstraZeneca) ( 15 , 16 ). A review reported 24 cases of keratitis in association with herpes zoster or varicella vaccination ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Keratitis in association with vaccines appeared to be uncommon. Furthermore, three cases of herpes simplex virus (HSV) keratitis were reactivated after COVID-19 vaccination (2 of 3 were associated with BNT162b2 mRNA vaccination, the third one was AstraZeneca) ( 15 , 16 ). A review reported 24 cases of keratitis in association with herpes zoster or varicella vaccination ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…A review reported 24 cases of keratitis in association with herpes zoster or varicella vaccination ( 17 ). Two possible mechanisms involved in the pathogenesis included molecular mimicry and autoinflammation triggering the host response and promoting the HSV replication ( 16 ). Hence, the treating physician should be mindful of such associations between vaccination and keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Different post vaccination side effects have been described in the recent literature and drug’s leaflet. Thrombosis of different types [ 1 , 9 , 13 , 17 , 18 ] and exacerbation of underlying herpetic disease [ 8 – 11 , 13 , 19 ] are among the most common. The same was observed in our case series.…”
Section: Discussionmentioning
confidence: 99%
“…Before our cases, there was only one report of HSK recurrence after receiving an adenovirus-vectored COVID-19 vaccine (Astra-Zeneca). According to these few existing reports, ocular adverse event manifestations occurred within two weeks of COVID-19 vaccination and can appear as early as the day after vaccination [6][7][8][9]13,16]. Various types of COVID-19 vaccines such as mRNA vaccine [7], inactivated vaccine [9] and recombinant vector vaccine [16] can all be involved.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a temporary decrease of cell-mediated immunity during the early period post vaccination may be involved. Other proposed mechanisms include molecular mimicry and the distraction of the humoral response [16,22].…”
Section: Discussionmentioning
confidence: 99%